Possibilities of preserving reproductive function in female patients with atypical hyperplasia and endometrial cancer at an early stage - O.F. Serova; Yu.E. Dobrokhotova; E.I. Borovkova; A.V. Charkhifalakyan (LCC «Medicine-Inform», 2023)
O.F. Serova1, Yu.E. Dobrokhotova2, E.I. Borovkova2, A.V. Charkhifalakyan3 1Burnasyan Federal Medical Biophysical Center of Federal Medical Biological Agency, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3European Medical Center, Moscow, Russian Federation Due to the childbearing shift to the fourth decade of life, the probability of detecting endometrial cancer (EС) in female patients who did not have time to realize their reproductive life plan increases. If cancer is detected in female patients of reproductive age and they want to realize their fertility in the future, this option should be considered at the stage of treatment planning. Discussion concerning the admissibility and safety of conservative EC treatment is extremely relevant in the current demographic conditions. The article considers the decision-making algorithm on the conservative therapy indication in the cancer manifestation in a female patient of reproductive age with unrealized fertility, as well as the protocol when making such a decision. Data on the frequency of pregnancy in female patients after conservative treatment of EC are given. The accumulated experience showed that drug treatment of atypical hyperplasia and initial EC is effective, and upon condition of subsequent pregnancy does not aggravate the oncological prognosis. Keywords: endometrial cancer, uterine cancer, atypical hyperplasia, pregnancy, assisted reproductive technologies, conservative therapy. For citation: Serova O.F., Dobrokhotova Yu.E., Borovkova E.I., Charkhifalakyan A.V. Possibilities of preserving reproductive function in female patients with atypical hyperplasia and endometrial cancer at an early stage. Russian Journal of Woman and Child Health. 2023;6(4):-361 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-5.